Mubadalah dan Hadis Gender: Studi Pemikiran Faqihuddin Abdul Qadir - Iqro’ Katsir; Romlah Abubakar Askar; Abdul Ghofur (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This study departs from the mubadalah approach in interpreting hadiths related to gender relations from the perspective of Faqihuddin Abdul Qadir's thought. Through a literature review and descriptive-analytical analysis method, this research examines how mubadalah, as a hermeneutic method, can offer a fair, contextual, and equitable reading of religious texts. In Faqihuddin's view, mubadalah is based on the principles of reciprocity and mutual relations between men and women, rejecting both gender hegemony and subordination. This approach serves as a critical response to the patriarchal constructions in Islamic interpretations that have marginalized women. The findings indicate that mubadalah can bridge the gap between conservative textual approaches and radical liberal readings, and is relevant for realizing justice and gender equality in the lives of Muslims